Modern Technological Approaches for Ensuring of Harmless and Quality Fruits - Miteva, D., Institute of Cryobiology and Food Technology, Sofia (Bulgaria); Dimov, K., Institute of Cryobiology and Food Technology, Sofia (Bulgaria); Nacheva, I., Institute of Cryobiology and Food Technology, Sofia (Bulgaria); Todorov, Y., Institute of Information and Communication Technologies, BAS, Sofia (Bulgaria); Doneva, M., Institute of Cryobiology and Food Technology, Sofia (Bulgaria); Metodieva, P., Institute of Cryobiology and Food Technology, Sofia (Bulgaria); Tsvetkov, Ts., Institute of Cryobiology and Food Technology, Sofia (Bulgaria) (Bulgarian Journal of Agricultural Science (Bulgaria), 2014)
The problem of the rational use of the food sources and their long-term preservation is of particular importance. Modern technologies offer a solution of this problem by applying of new methods for fruits preservation. Gamma sterilization is identified as a safe technology for reducing the risk of spoilage and prolongation of the storage term. It has been proved that the low irradiation doses are appropriate for fruits processing, which is a prerequisite for obtaining of high quality produce. In the present study was investigated the effect of the irradiation with low gamma ray doses - 2.5?3.5 ÐºGy on the chemical and microbiological characteristics of fruits not subject to long-term storage. By irradiation of packed strawberries and raspberries with 2.5 ÐºGy dose the refrigerated storage term is prolonged with 12?13 days, which is of substantial importance for preserving of their quality characteristics.